2021
DOI: 10.1021/acs.biochem.1c00672
|View full text |Cite
|
Sign up to set email alerts
|

Human Mat2A Uses an Ordered Kinetic Mechanism and Is Stabilized but Not Regulated by Mat2B

Abstract: Methionine adenosyltransferase (MAT) catalyzes the adenosine 5′-triphosphate (ATP) and l-methionine (l-Met) dependent formation of S-adenosyl-l-methionine (SAM), the principal methyl donor of most biological transmethylation reactions. We carried out in-depth kinetic studies to further understand its mechanism and interaction with a potential regulator, Mat2B. The initial velocity pattern and results of product inhibition by SAM, phosphate, and pyrophosphate, and dead-end inhibition by the l-Met analog cyclole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…MAT2B has been suggested to regulate MAT2A in low methionine or high methionine conditions by respectively activating or inhibiting MAT2A activity ( 95 ). Other data have suggested that the presence of MAT2B does not affect MAT2A activity but does improve MAT2A stability and longevity in low substrate concentrations ( 98 ). Therefore, these data suggest that the capacity of MAT2A inhibition via PF-9366 may be dependent on MAT2B levels or methionine/ATP availability.…”
Section: Pharmacological Prmt5/mat2a Inhibition and Selectivity For M...mentioning
confidence: 99%
“…MAT2B has been suggested to regulate MAT2A in low methionine or high methionine conditions by respectively activating or inhibiting MAT2A activity ( 95 ). Other data have suggested that the presence of MAT2B does not affect MAT2A activity but does improve MAT2A stability and longevity in low substrate concentrations ( 98 ). Therefore, these data suggest that the capacity of MAT2A inhibition via PF-9366 may be dependent on MAT2B levels or methionine/ATP availability.…”
Section: Pharmacological Prmt5/mat2a Inhibition and Selectivity For M...mentioning
confidence: 99%
“…Although many previous studies have shown that MAT2B can regulate MAT2A activity by changing its substrate affinity and sensitivity to product inhibition, 17−20 some studies have also demonstrated that the binding of MAT2B to MAT2A has no significant effect on the catalytic activity of MAT2A or physiologically relevant inhibition of SAM, meaning that the regulation of MAT2A activity by MAT2B does not appear to be direct and likely occurs through an unknown mechanism. 21 In addition, MAT2B interacts with many proteins that affect cell growth and signaling pathways. 22−28…”
Section: Mat Familymentioning
confidence: 99%
“…MAT1 is a tetramer of MAT1A whereas MAT3 is a dimer of MAT1A (16, 17). MAT2 is composed of the catalytic subunit MAT2A and the regulatory subunit MAT2B that stabilizes MAT2A (1618). MAT1 and MAT3 are expressed in the liver whereas MAT2 is expressed in almost all tissues of the body, developing liver and hepatocellular carcinoma but not in the normal liver (15, 19).…”
Section: Introductionmentioning
confidence: 99%